Duckling? No, Swan! Non-native Teachers Teaching Spoken English to Non-native Learners - Jayashree Mohanraj (International Conference on Education and Language (ICEL), 2013)
English has been accepted as a global language. Users of English as a second language have outnumbered the native speakers. David Crystal gives the statistics which say that second/foreign language users of English are in the range of 1000 million, whereas the native speakers total not more than 400 million (Crystal, D 2004). As a result, teaching of English has acquired greater importance in the 21st century. The goals of teaching English have acquired new dimensions. In this context many issues and questions arise in teaching English, especially in teaching spoken English because a major part of communication transpires through the spoken mode.Non-native speakers learning to speak English from native speaker teachers in the English environment get a lot of support. But non-native teachers teaching and testing spoken English to non-native learners in a second language context is very challenging. The teacher has to take several decisions like which model to adopt – RP or American or the non-native variety. If a non-native variety is adopted, which one? In the multi-lingual context the teacher should also be aware of the mother tongue in the learners’ English. Besides this, the decision about the importance to be given to accuracy and fluency gains relevance in the context of communication in English. Other considerations are the availability of readymade materials and the teacher competence in filling the gaps if suitable materials are not available. Sometimes the problems include the learners’ reluctance to accept the non-native teachers.The paper discusses the principles and issues involved in teaching spoken English. The paper argues that teaching spoken English by non-native teachers to non-native learners in multi-lingual context is more challenging than teaching other skills. The author’s experience in teaching spoken English to undergraduates in Eritrea and Yemen and also students from various countries studying at the English and Foreign Languages University, and how the challenges are met would be discussed.